Legal and Ethical Implications of Unilateral Cancellation of Naming Rights: A Case Study of PT KAI and BT Batik Trusmi Cirebon - Siti Sopyah; Rani Dewi Kurniawati (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2025)
This study aims to analyze the legal and ethical implications of the unilateral cancellation of naming rights by PT Kereta Api Indonesia (Persero) against BT Batik Trusmi Cirebon, as well as to examine its implications for partnership practices between state-owned enterprises (SOEs) and the private sector in Indonesia. This study uses a legal-empirical approach, combined with a business ethics approach to assess the moral dimensions and social responsibility of corporate decisions. The results of the study show that unilateral cancellation violates the principle of pacta sunt servanda as stipulated in Article 1338 of the Civil Code and has the potential to cause a breach of contract in accordance with Article 1243 of the Civil Code because it was not done based on mutual agreement and without a valid settlement mechanism. This action also violates the principle of good faith, which requires the parties to act honestly and fairly in executing the agreement. From a business ethics perspective, this unilateral cancellation reflects the moral failure of corporations in applying the principles of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR), which is characterized by a lack of transparency, accountability, and social responsibility in the decision-making process. This situation has caused a crisis of trust between state-owned enterprises and private partners and has damaged the moral legitimacy of state-owned enterprises as public entities.